2018
DOI: 10.3390/s18051463
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Detection of Respiration and Heart Rate with a Vehicle Seat Sensor

Abstract: This study demonstrates the feasibility of using a seat sensor designed for occupant classification from a production passenger vehicle to measure an occupant’s respiration rate (RR) and heart rate (HR) in a laboratory setting. Relaying occupant vital signs after a crash could improve emergency response by adding a direct measure of the occupant state to an Advanced Automatic Collision Notification (AACN) system. Data was collected from eleven participants with body weights ranging from 42 to 91 kg using a For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…In 2018, Wusk and Gabler [ 74 ] introduced an estimate of the cardiorespiratory function obtained using the BCG sensor in the passenger seat of the Ford Mustang, where the authors suggested using a “fluid-filled bladder attached to a solid-phase pressure transducer” as a sensor. The study contained the data collected from eleven volunteers, and the whole study was carried out in controlled laboratory conditions.…”
Section: Overview Of Already Existing Methodsmentioning
confidence: 99%
“…In 2018, Wusk and Gabler [ 74 ] introduced an estimate of the cardiorespiratory function obtained using the BCG sensor in the passenger seat of the Ford Mustang, where the authors suggested using a “fluid-filled bladder attached to a solid-phase pressure transducer” as a sensor. The study contained the data collected from eleven volunteers, and the whole study was carried out in controlled laboratory conditions.…”
Section: Overview Of Already Existing Methodsmentioning
confidence: 99%
“…Very recently, in 2018, Wusk and Gabler presented heart and respiratory rate estimation obtained with a BCG sensor in a Ford Mustang passenger seat [ 78 ]. As a sensor, the authors proposed using a “fluid filled bladder connected to a solid-state pressure transducer”.…”
Section: Ballistocardiographymentioning
confidence: 99%
“…To this aim, Ref. [7] from Virginia Tech, USA, demonstrates the feasibility of using a seat sensor designed for occupant classification from a production passenger vehicle to measure an occupant’s respiration rate (RR) and heart rate (HR). Relaying occupant vital signs after a crash could improve emergency response by adding a direct measure of the occupant state to an Advanced Automatic Collision Notification (AACN) system.…”
Section: Review Of the Contributions In The Special Issuementioning
confidence: 99%
“…The proposed special issue has invited submissions related to sensing and connectivity systems for assisted and autonomous driving and for unmanned aerial, underwater and ground vehicles (namely UAV, UUV and UGV) [1,2,3,4,5,6,7,8,9,10,11,12]. Recent studies on the future of the automotive and robotic industry predict that the borders between the ICT (Information and Communication Technology) industry and the consumer industry will blur, and that vehicles will become consumer-centric [13].…”
Section: Introductionmentioning
confidence: 99%